Implikasi Krisis Pandemi Covid-19 Terhadap Etika Perusahaan: Prespektif Etis Corporate Social Responsibility - Khalilul Rahman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2022)
The COVID-19 pandemic resulted in a crisis that will test the company's commitment to ethical business conduct. The impact of the COVID-19 pandemic on the economy, health and society has increased sharply. Based on stakeholder theory, legitimacy theory and literature on corporate social responsibility (CSR), this paper attempts to explore how corporate responses to the COVID-19 pandemic support key stakeholders such as employees, customers and society as a whole through its CSR initiatives. The results of this paper are that corporations can show respect for their employees and focus on management relationships between companies, customers and communities during the COVID-19 pandemic. This will have significant theoretical implications and practical implications on corporate duties to employees, customers and society and future research on CSR as a competitive force for business even after the economic recession following the COVID-19 pandemic.